NEOLIBERAL VIEWS OF THE CHALLENGES OF THE NATION-STATE IN THE MODERN AGE - Šuleić, Jelena (Political Review, 2023)
The paper starts that the modern age is the period from the signing of the Treaty of Westphalia until today, and that the existing global system of collective security is a sufficient and reliable guarantor of preserving the sovereignty of the national state in the modern age. It can be a challenge for the state, and the perseverance facing the state will be considered more heavily in the political and economic dimension in the post-Cold War period. The aim of this paper is to observe at the theoretical definition of the national state, ie to present its key characteristics, which distinguishes the state from earlier forms of political organization. In order to indicate a brief historical overview of the development of the national state and the characteristics of international relations for the considered periods. The focus of the paper identifies the basic challenges faced by the national state in the post-Cold War period, with a focus on economic and political challenges. This is followed by a brief overview of the role of the United Nations (UN) in maintaining international peace and security in the post-Cold War period.